Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Hsu, Tien-Huan; Liu, Hao-Ping; Chin, Chieh-Yu; Wang, Chinling; Zhu, Wan-Zhen; Wu, Bing-Lin; Chang, Yu-Chung (Archives of virology, 2018)
Porcine deltacoronavirus (PDCoV) was initially documented in Hong Kong and later in the United States, South Korea, and Thailand. To investigate if PDCoV is also present in Taiwan, three swine coronaviruses-PDCoV, porcine epidemic diarrhea virus (PEDV), and transmissible gastroenteritis coronavirus (TGEV)-were tested using real-time reverse transcription polymerase chain reaction (rRT-PCR) in 172 rectal swab samples from piglets exhibiting diarrhea between January 2016 and May 2017 on 68 pig farms in Taiwan. The rRT-PCR results were positive for PDCoV (29/172, 16.9%), PEDV (36/172, 20.9%), TGEV (2/172, 1.2%), and coinfections (16/172, 9.3%). After cloning and sequencing, PDCoV nucleocapsid genes were analyzed. Phylogeny results indicated that the nucleotide sequences of all isolates were like those reported in other countries. To further trace PDCoV in the period of 2011 to 2015, an enzyme-linked immunosorbent assay (ELISA) was used to detect antibodies against PDCoV. The results showed that 279 of 1,039 (26.9%) sera were positive for the PDCoV nucleocapsid protein, implying that PDCoV might have existed in Taiwan before 2011.